Higher Education Governance in East Asia Transformations under Neoliberalism (Higher Education in Asia: Quality, Excellence and Governance,, 2018)
This book deepens our understanding of how higher education governance has recently changed in the rapidly developing higher education systems of East Asia. Focusing on China, Japan, Korea, Malaysia and Taiwan, it explains the implications of how state-centered political systems interpret political and economic environments such as neoliberalism, as well as how each system is coping with global pressures. The book makes a valuable contribution to organization studies in higher education by investigating and detailing how individual higher education institutions are responding to their new environments.